Child drowning: a nurse's approach to domestic accidents (Research, Society and Development, 2020)
The precaution of accidents that happen at home focusing on child drowning is a resource in which it depends on professional knowledge to be avoided, with guidance from a nurse regarding the indispensable measures for these events. It is necessary to apply efficient preventive measures in all levels of care, in primary prudence in order to reduce these accidents, with educational actions on these unexpected events. the actions elaborated and the results achieved. Object of study has as purpose the performance of the Nurse Facing the Needs of Home Care as drowning child. Objective to analyze the conduct of nurses in care with home care against child drowning. This study is justified by the causes and consequences of these events, I observed how essential is the measure related to preventive actions for this occurred.